Ultrasmall PbS quantum dots: a facile and greener synthetic route and their high performance in luminescent solar concentrators. Issue 21 (10th May 2017) - Tan, Long; Zhou, Yufeng; Ren, Fuqiang; Benetti, Daniele; Yang, Fan; Zhao, Haiguang; Rosei, Federico; Chaker, Mohamed; Ma, Dongling
Abstract : Tributylphosphine-assisted greener synthesis of ultrasmall PbS quantum dots and their high performance in luminescent solar concentrator application. Abstract : Synthesis of quantum dots (QDs) with widely size-tunable optical absorption and high photoluminescence quantum yield (PL QY) via a facile route is highly desired. By introducing tributylphosphine (TBP) into a relatively green synthesis method based on the use of S, PbCl2 and oleylamine (OLA), we conveniently synthesized ultrasmall PbS QDs with the first excitonic absorption peak wavelength as short as 705 nm, without using a glove box, which cannot be achieved by previously reported approaches, without involving smelly S precursors (such as bis(trimethylsilyl) sulfide). Such synthesized PbS QDs show narrow size distributions without any aggregation and demonstrate high PL QY in the range of 60–90%, depending on the QD size. Based on nuclear magnetic resonance spectroscopy and X-ray diffraction investigations, TBP was found to act as the passivation ligand on the surface of QDs while simultaneously assisting the transformation of PbCl2 –OLA into more reactive Pb(OH)Cl that can directly participate the nucleation process, yielding ultrasmall PbS QDs. This new finding renders Pb(OH)Cl a very promising, new lead precursor for convenient synthesis of PbS and other lead-based QDs. We also demonstrate that the process can be readily scaled up. After synthesizing a thin CdS shell (∼0.1 nm), ultrasmall core/shell QDs with a large Stokes shift (0.36 eV) and good stability were employed for fabricating near infrared (NIR) luminescent solar concentrators, which led to a record-high optical efficiency of ∼1.2% at a geometric factor of ∼50 (10 cm in length). The TBP route developed herein is very promising for synthesizing high quality ultrasmall QDs that have high potential in NIR-related applications.